2012
DOI: 10.1259/bjr/70496948
|View full text |Cite
|
Sign up to set email alerts
|

Signal-to-noise ratio increase in carotid atheroma MRI: a comparison of 1.5 and 3 T

Abstract: Objectives: This study reports quantitative comparisons of signal-to-noise ratio (SNR) at 1.5 and 3 T from images of carotid atheroma obtained using a multicontrast, cardiacgated, blood-suppressed fast spin echo protocol. Methods: 18 subjects, with carotid atherosclerosis (.30% stenosis) confirmed on ultrasound, were imaged on both 1.5 and 3 T systems using phased-array coils with matched hardware specifications. T 1 weighted (T 1 W), T 2 weighted (T 2 W) and proton density-weighted (PDW) images were acquired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…[13][14][15] Most CPI has been performed at 1.5T, although a few recent studies have used 3T. Similar relative appearances on multi-contrast techniques [18][19][20][21] have been report at 1.5T and 3T.…”
Section: Introductionmentioning
confidence: 80%
“…[13][14][15] Most CPI has been performed at 1.5T, although a few recent studies have used 3T. Similar relative appearances on multi-contrast techniques [18][19][20][21] have been report at 1.5T and 3T.…”
Section: Introductionmentioning
confidence: 80%
“…In this study only PDWI images were analyzed because these have the best signal-to-noise ratio (SNR). These data were demonstrated by Young et al (26), who found that in the 3T systems the PDWI also shows the best SNR in the carotid artery wall/ plaque. In another article by Biasiolli et al (27), it was found that the PDWI images have a reduced blur edge.…”
Section: Discussionmentioning
confidence: 55%
“…However, the inferior field strength in a head-to-head comparison has proven to be equally utilizable for morphometric measurements, despite lower signal-to-noise ratios. 25,26 Our method for patient selection using ultrasonography to detect common CA stenosis may have yielded a heterogeneous group of patients. Since carotid ultrasound measurement of plaque only includes the interior quadrant of the CA, this technique may overestimate the actual stenosis rate as measured by MRI.…”
Section: Study Limitationmentioning
confidence: 99%